2021
DOI: 10.1192/bjb.2021.67
|View full text |Cite
|
Sign up to set email alerts
|

Teaching psychiatry to medical students in the time of COVID-19: experiences from UK medical schools

Abstract: Aims and method Education leads for undergraduate psychiatry in UK medical schools completed questionnaires on adaptations made to undergraduate psychiatry education, their impact and what lessons could be learnt for the future. Results Respondents from 24 medical schools across the UK reported a major shift to online teaching delivery, with reduced workplace learning and increased use of teleconferencing, online tasks and self-directed learning. Changes were implemented with some facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Similarly, a recent study reported that two-thirds of medical schools made no alterations to the duration of psychiatry modules during COVID-19, while 12.5% increased and 20.8% reduced them. 27 Some of our surveyed medical schools expressed plans to implement blended teaching models, combining face-to-face and virtual learning postpandemic. This is echoed in other research, where 87.5% of medical schools reported long-term changes to psychiatry teaching persisting beyond the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a recent study reported that two-thirds of medical schools made no alterations to the duration of psychiatry modules during COVID-19, while 12.5% increased and 20.8% reduced them. 27 Some of our surveyed medical schools expressed plans to implement blended teaching models, combining face-to-face and virtual learning postpandemic. This is echoed in other research, where 87.5% of medical schools reported long-term changes to psychiatry teaching persisting beyond the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This is echoed in other research, where 87.5% of medical schools reported long-term changes to psychiatry teaching persisting beyond the pandemic. 27 Online psychiatry teaching and virtual placement activities, given their scalability, may support the planned expansion of medical undergraduate numbers in the UK by increasing teaching capacity. 28 The MLA should standardise undergraduate medical curricula since UK medical schools will be required to 'map' their curriculum to this examination.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Specifically for psychiatry training, medical students in the United Kingdom experienced reduced educational demands such as experience documentations, attendance monitoring, workplace-based assessments, and case presentations, but noted no lowering or compromised of clinical standards. 24 Final year medical students in Sri Lanka also reported great impacts on psychiatric training and exam performance. The pandemic had impacts on clinical aspects including patient availability, mental status assessments, rapport development, diagnostic skills, and clinical exam components.…”
Section: Discussionmentioning
confidence: 99%
“…In an online survey of students at eight medical schools in Sri Lanka, students rated digital lecture formats in psychiatry as an effective teaching method [31]. A survey of 24 responsible persons for psychiatric teaching at medical schools in the United Kingdom also indicates a high level of satisfaction with digital teaching in psychiatry on the part of students [32]. To our knowledge, our study is the only one to evaluate knowledge gain, teaching contents and subjective advantages of this teaching format in psychiatry for two consecutive summer semesters.…”
Section: Plos Onementioning
confidence: 99%